Computing fundamentals : IC3 edition - Wempen, Faithe (Wiley, 2014)
Kick start your journey into computing and prepare for your IC3 certification With this essential course book you'll be sending e-mails, surfing the web and understanding the basics of computing in no time. Written by Faithe Wempen, a Microsoft Office Master Instructor and author of more than 120 books, this complete guide to the basics has been tailored to provide comprehensive instruction on the full range of entry-level computing skills. It is a must for students looking to move into almost any profession, as entry-level computing courses have become a compulsory requirement in the m.